Flow Regimes and Transitions for Two-Phase Flow of R152a During Condensation in a Circular Minichannel - Liu, Na; Zhao, Qian; Lan, Zhixiang (Frontiers in Energy Research, 2021)
Two-phase flow regimes were experimentally investigated during the entire condensation process of refrigerant R152a in a circular glass minichannel. The inner and outer diameters of the test minichannel were 0.75 and 1.50 mm. The channel was 500 mm long to allow observation of all the two-phase flow regimes during the condensation process. The experiments used saturation temperatures from 30 to 50°C, a mass flux of 150 kg/(m2·s) and vapor qualities from 0 to 1. The annular, intermittent and bubbly flow regimes were observed for the experimental conditions in the study. The absence of the stratified flow regime shows that the gravitational effect is no longer dominant in the minichannel for these conditions. Vapor-liquid interfacial waves, liquid bridge formation and vapor core breakage were observed in the minichannel. Quantitative measurements of flow regime transition locations were carried out in the present study. The experiments also showed the effects of the saturation temperature and the cooling water mass flow rate on flow regime transitions. The results show that the annular flow range decreases and the intermittent and bubbly flow ranges change little with increasing saturation temperature. The cooling water mass flow rate ranging from 38.3 kg/h to 113.8 kg/h had little effect on the flow regime transitions.